Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12906
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

The most beautiful job in the world: lifting the veil on the fashion industry - Mensitieri, Giulia; Lehrer, Natasha (Bloomsbury Visual Arts, Bloomsbury Publishing Plc, 2020)
Keywords: Fashion; Myriam